Studi di catalanistica in Italia (2005-2014 circa). - COMPAGNA, ANNA MARIA; BAFALUY, NÚRIA PUIGDEVALL (Scripta, 2015)
This article provides an overview of Catalan studies carried out in Italy, based on the recent contribution offered in the RISCAT, journal of the Catalan Studies Italian Association.